Effects of Paper-Mill Sludge as a Mulch versus Topsoil Incorporation on Potassium Uptake and the Grain Yield of Rain-Fed Wheat in a High Specific Surface Loess Soil with Illite Dominance in Clay Fraction - Amini, S.; Movahedi Naeini, S. A. R.; Mashayekhi, K. (Applied and Environmental Soil Science, 2012)
A field experiment with rain-fed winter wheat investigated the nutritional aspects of paper-mill sludge as a mulch and incorporated into the topsoil. Treatments with chemical fertilizers were also used as controls. Paper-mill sludge used as mulch with high rate (100 MG ha−1) and also the combined N and K mineral fertilizer treatments increased yield when a low potassium otherwise caused potassium deficiency in wheat with high specific surface soil. High soil Ca : K molar ratio by incorporation lowered potassium uptake and yield, with visual symptoms of potassium deficiency. A very high Gapon selectivity coefficient (KG) for K exchange against Ca + Mg (16.58 (L/mole)0.5) produced a nonlinear normalized exchange isotherm in favor of potassium with these soils containing high illite. Ca and K which are released by sludge decomposition are diverged in soil when mobilized by rain infiltration, lowering Ca : K molar ratio. Low soil Ca : K molar ratio may be expected by surface sludge application relative to incorporation, due to greater rain infiltration through upper soil layers and their effluent pore volumes per unit depth. Ca from triple superphosphate by the P, N, and K mineral fertilizers combined also reduced potassium uptake and yield relative to N and K combined.